1998
DOI: 10.1097/00001756-199801050-00010
|View full text |Cite
|
Sign up to set email alerts
|

Postural control, attention and sleep deprivation

Abstract: We investigated the effect of sleep deprivation on postural control during a simple reaction time task (SRT), during a task requiring the intermittent inhibition of a reaction (IRT), and in the absence of a concurrent information processing task. Postural sway, i.e. changes in center of pressure on a force platform, was recorded in three increasingly difficult standing conditions (fixed platform, sway-referenced platform and sway-referenced platform with sway-referenced visual scene) during the three informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 6 publications
2
63
2
Order By: Relevance
“…In the present study, sporting activities and do-it-yourself and gardening activities were found to especially reduce the risk of falls. Sport and physical training improve the quality of postural control [39][40][41] by developing neurosensorial information sensitivity which promotes anticipatory postural adjustments. Practicing physical activity allows faster detection of destabilization and the organization of compensatory mechanisms to avoid falls.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, sporting activities and do-it-yourself and gardening activities were found to especially reduce the risk of falls. Sport and physical training improve the quality of postural control [39][40][41] by developing neurosensorial information sensitivity which promotes anticipatory postural adjustments. Practicing physical activity allows faster detection of destabilization and the organization of compensatory mechanisms to avoid falls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have also indicated that postural stability (Liu et al, 2001;Nakano et al, 2001;Avni et al, 2006) and motor control (Frey et al, 2004) are affected by sleep deprivation, though the mechanisms have yet to be determined. Some consider that the motor deficits are caused by alterations in the attentional state of the brain (Schlesinger et al, 1998;Fabbri et al, 2006). Other authors have proposed that detrimental postural effects are the result of daily circadian changes involving alertness (Nakano et al, 2001;Gribble and Hertel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Schlesinger et al [12] emphasised that complex balance movements require more concentration and attention, and therefore the sleep state of participants is important. In our study, the test performance did not show a difference at different times of the day for either leg in terms of chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…The participants' dynamic balance performances were determined using the Star Excursion Balance Test (SEBT), whose validity and reliability has been proven [20] and which is widely used among young adults (aged 18-25 years) [9,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation